Biodegradation of Crude Oil and Aniline by Heavy Metal-Tolerant Strain Rhodococcus sp. DH-2 - Zetian Luo; Jiajun Ma; Lei Huang; Dahui Li; Guohui Gao; Yihe Zhao; Agostinho Antunes; Meitong Li (Microorganisms)
Aniline and crude oil are common environmental pollutants that present a significant risk to both the ecological and human health environments. The implementation of efficacious bioremediation strategies is imperative for the elimination of these contaminants. In this study, a bacterial strain designated DH-2 was isolated from soil contaminated with aniline. The strain was identified as belonging to the genus Rhodococcus. The optimal conditions for the growth and aniline degradation by strain DH-2 were determined to be pH 8.0 and 35 °C, respectively. Under these conditions, the degradation rate of aniline at a concentration of 1000 mg/L exceeded 90% within 36 h. Even in the presence of 4% NaCl, the degradation rate remained above 60%. HPLC–MS analysis revealed that the aniline degradation pathway of strain DH-2 follows the catechol pathway. Additionally, strain DH-2 is capable of utilizing crude oil as the sole carbon source, achieving a degradation rate of 91.0% for 2% crude oil concentration within 4 days. In soil modeling experiments, strain DH-2 was observed to degrade aniline and crude oil under triple stress conditions, including 1000 mg/L aniline, 2% crude oil, and 20 mg/L Fe(II) or Pb(II). Complete degradation of aniline and crude oil was achieved after 3 days and 12 days, respectively. The addition of Fe(II) or Pb(II) ions was found to enhance the degradation ability of DH-2. These results demonstrate that strain DH-2 is an extremely effective biodegradable strain, with potential applications in the remediation of environments contaminated with aniline and crude oil, even in the presence of heavy metals.